2014
DOI: 10.1126/science.1248882
|View full text |Cite
|
Sign up to set email alerts
|

Defining an essential transcription factor program for naïve pluripotency

Abstract: The gene regulatory circuitry through which pluripotent embryonic stem (ES) cells choose between self-renewal and differentiation appears vast and has yet to be distilled into an executive molecular program. Here we developed a data-constrained, computational approach to reduce complexity and derive a set of functionally validated components and interaction combinations sufficient to explain observed ES cell behavior. This minimal set, the simplest version of which comprises only 16 interactions, 12 components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
523
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(552 citation statements)
references
References 42 publications
26
523
1
2
Order By: Relevance
“…ES cells in 2iLIF were compared to cells cultured without MEK inhibition in medium containing GSK3 inhibitor, Chir99021 (CH), plus LIF (CHLIF). This allows analysis of the ERK‐responsive phosphoproteome independent of a change in identity because ES cells withstand ERK signalling and remain undifferentiated in CHLIF 7, 19, 20.…”
Section: Resultsmentioning
confidence: 99%
“…ES cells in 2iLIF were compared to cells cultured without MEK inhibition in medium containing GSK3 inhibitor, Chir99021 (CH), plus LIF (CHLIF). This allows analysis of the ERK‐responsive phosphoproteome independent of a change in identity because ES cells withstand ERK signalling and remain undifferentiated in CHLIF 7, 19, 20.…”
Section: Resultsmentioning
confidence: 99%
“…Variation in gene expression dynamics between the two differentiation trajectories suggested that these orderings could be used to help understand differences between the regulatory programs controlling differentiation toward alternative blood fates. Previous studies have successfully used Boolean abstraction to model transcriptional regulatory networks in HSCs (23), embryonic blood development (10), and embryonic stem cells (8,24).…”
Section: Resultsmentioning
confidence: 99%
“…An advantage of Boolean network modeling, as used in this work, is that it does not suffer from this limitation. A recent study used Boolean abstraction to model the pluripotency network in embryonic stem cells (24), and was able to predict the results of experimental network perturbations. However, this study relied on performing gene expression profiling in multiple experimental conditions, which is not always feasible, and was limited to bulk rather than single-cell data.…”
Section: Discussionmentioning
confidence: 99%
“…It would be tempting to explore the different logical rules in a more unsupervised way by building all possible models with all combinations of regulations and testing their accuracy in silico. Although this approach has been used previously (37), it can be applied only to a subset of possible combinations (e.g., testing the addition or removal of regulations under a general logical rule, such as requiring all activators but none of the inhibitors to enable the activation of a component) and impose certain technical constraints (e.g., limitation to Boolean variables or to synchronous updating). In this study, we first built a model based on published data and then used it to identify caveats in our current knowledge; these caveats then were addressed by exploiting relevant highthroughput datasets.…”
Section: Discussionmentioning
confidence: 99%